The semiconductor community in the Silicon Valley: a network analysis of the SEMI genealogy chart (1947–1986). (1st January 2003) - Assimakopoulos, Dimitris; Everton, Sean; Tsutsui, Kiyoteru
This paper focuses on the emergence of an informal, collaborative and entrepreneurial organisational culture within the technological community of semiconductor firms in the Silicon Valley, California. Using recently developed computerised network analysis techniques and a genealogy chart of Silicon Valley semiconductor firms, it demonstrates how a new democratic community, rather than a hierarchical workplace, organisational culture was firstly initiated with the foundation of Fairchild Semiconductor back in 1957, and more importantly, how this new culture was diffused through successive generations of "Fairchildren" spin-offs, up to the mid-1980s. In the process of critical mass formation they also identified the most central companies in the semiconductor community, including the usual suspects, Fairchild, Intel and Hewlett-Packard, but also a relatively unknown firm outside the semiconductor community, Intersil Co.